Genetic diversity in rosewood saplings (Aniba rosaeodora ducke, Lauraceae): an ecological approach - Santos, Ronaldo Pereira; Spironello, Wilson Roberto; Sampaio, Paulo de Tarso Barbosa (Acta Amazonica, 2008)
This article takes an ecological approach to the genetic diversity of Rosewood (Aniba rosaeodora Ducke) in a central Amazonian terra firme forest north of Manaus. Planted Rosewood setting, under partial shaded canopy, were assessed in terms of fruiting production, frugivory, and seed dispersal. Using RAPD molecular analysis procedures, the influence of the spatial distribution of adult trees on the genetic diversity (polymorphism) of saplings was assessed with genetic samples from 34 reproductive trees and 60 saplings. The density and distribution patterns the reproductive trees did not modify the sapling"s diversity (1.86%, AMOVA). Two types of adult tree dispersion were identified; i) clumped and ii) more widely dispersed. Polymorphism (77.5%) and gene flow were high between these. Although more sapling genetic variability in areas with a higher density of mature plants was not as high as expected, density did not affect the genetic diversity of samplings, indicating a high incidence of gene flow amongst trees. In planted Rosewood population (surrounded by low disturbed forest), fruiting trees experienced a high level of removal of seeds by toucans (Rhamphastidae), about of 50%. The high gene flow found among native trees suggested that toucans, promoting seed rain at short and long distances from maternal trees, actively contribute to the maintenance of genetic diversity within wild rosewood populations.
Diversidade genética em plantas jovens de Pau-rosa (Aniba rosaeodora Ducke, Lauraceae): uma abordagem ecológica
Keywords: Amazonian Tree; Rapd; Seed Dispersal; Gene Flow; Genetic Diversity; Árvore Amazônica; Rapd; Dispersão De Sementes; Fluxo Gênico; Diversidade Genética